English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

assume that X is a positive number use the logarithm properties to present the expression log (x+2) - log X as the logarithm of a single quantity.


Please help

2007-03-28 03:39:53 · 2 answers · asked by Anonymous in Science & Mathematics Mathematics

2 answers

log(a) + log(b) = log(ab)
-log(a) = log(a^-1)

So,

log(x+2) +log(x^-1) = log [(x+2) * x^-1] = log[(x+2)/x] = log(1 + 2/x)

2007-03-28 03:44:37 · answer #1 · answered by jimvalentinojr 6 · 0 0

log(x) - log(y) = log(x/y)

log(x+2) - log(x) = log ((x+2)/x) = log (1 + (2/x))

2007-03-28 03:43:37 · answer #2 · answered by Dave 6 · 0 0

fedest.com, questions and answers